2011
DOI: 10.1016/j.foodchem.2011.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antioxidant activity of passion fruit (Passiflora edulis and Passiflora alata) extracts on stimulated neutrophils and myeloperoxidase activity assays

Abstract: The antioxidant activity of methanol extracts from Passiflora edulis and Passiflora alata pulp, and P. edulis rinds, healthy or infected with the passion fruit woodiness virus (PWV), was investigated using the oxidant activities of the neutrophil and the neutrophil granule enzyme myeloperoxidase (MPO), both playing key roles in inflammation. The reactive oxygen species produced by stimulated neutrophils were evaluated by lucigenin-enhanced chemiluminescence (CL) and the activity of purified MPO was measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 31 publications
(40 reference statements)
1
43
0
7
Order By: Relevance
“…Compounds that possess antioxidant activity have the ability to inhibit MPO level, and thus suppress oxidative damage and may consequently, prevent inflammatory conditions. 23) Histopathological examination revealed that the mucosa of mefenamic acid group as well as groups treated with compounds 4a-e, h, and j showed higher staining for myeloperoxidase enzyme compared to the vehicle group (Figs. 2A, B).…”
Section: Resultsmentioning
confidence: 98%
“…Compounds that possess antioxidant activity have the ability to inhibit MPO level, and thus suppress oxidative damage and may consequently, prevent inflammatory conditions. 23) Histopathological examination revealed that the mucosa of mefenamic acid group as well as groups treated with compounds 4a-e, h, and j showed higher staining for myeloperoxidase enzyme compared to the vehicle group (Figs. 2A, B).…”
Section: Resultsmentioning
confidence: 98%
“…The latter effect is explained by the increase of NO, which reduces the CVD risk (Sano et al 2011). There have also been similar studies with passion fruit skin that also showed positive results as a potential source of antioxidant (Wong et al 2014, Zeraik et al 2011. Studies show that passion fruit has another bioactive compound named pectin, which significantly reduces neutrophil infiltration and partially decreases TNF-α (Silva et al 2011, Yapo andKoffi 2006).…”
Section: Piceatannol and Scirpusin Bmentioning
confidence: 85%
“…The synthesis of NOX and MPO, and ROS generation in activated neutrophils have been reported to be affected by certain polyphenols. 2,23,27,28,[30][31][32] Accordingly, the suppression of MPO-and activated neutrophilinduced chlorination of Guo shown by plant polyphenols must relate to the actions of NOX or MPO. These phenomena might have to do with the reduction of neutrophil functioning as in respiratory burst, ROS production, MPO release, and the assembly of enzymes by phenolic compounds.…”
Section: Discussionmentioning
confidence: 99%